Home-field advantage or a matter of ambiguity aversion? Local bias among German individual investors - Markus Baltzer; Oscar Stolper; Andreas Walter (Deutsche Bundesbank, 2011)
We analyze the effect of geographic proximity on individual investors' portfolio choice. Using a unique data set which covers the common stockholdings of private households at regional banks in Germany, we document strong and consistent overinvestment in geographically close companies. Our results conclusively reject the presence of an informational advantage ('home-field advantage') of local over non-local investors. Instead, households' preference for local equity turns out to be familiarity-driven. We conclude that individual investors' local bias is induced by ambiguity aversion in the portfolio selection process rather than a trading strategy based on superior information about local companies.
Keywords: G01; G11; G14; 330; local bias; portfolio diversification; household finance; investor behaviour; ambiguity aversion